Antibacterial efficacy of Solanum muricatum aiton metabolites against methicillin-resistant staphylococcus aureus: Insights into bioactive compounds and molecular mechanisms - Sarah Samir; Fathy A. Behery; Mohamed A. Zarka; Ruqaiah I. Bedaiwi; Hesham A. Abou-Zied; Usama Ramadan Abdelmohsen; Rehab Mahmoud Abd El-Baky; Mohamed A. Mawhoup; Mai Mahrous; Reem E. S. Abdelnaem; Gerhard Bringmann; Abeer H. Elmaidomy (PLoS ONE, 2025)
The incidence of methicillin-resistant Staphylococcus aureus (MRSA) has been steadily increasing in Ethiopia over the past few decades. As a result, the need for new antibiotic classes has become imperative to combat the growing threat of multidrug-resistant bacteria, including MRSA. Phytochemical investigation of the aerial parts extract of the edible plant Solanum muricatum Aiton (F. Solanaceae) afforded eight known metabolites: kaempferol 3- O -gentiobioside ( 1 ), kaempferol 3- O -sambubioside ( 2 ), quercetin 3- O -rhamnoside ( 3 ), procyanidin A2 ( 4 ), procyanidin A2 3- O -glucoside ( 5 ), (2 S )-2-hydroxy-3-[(9 Z ,12 Z )-1-oxo-9,12-octadecadien-1-yl]oxy]propyl- O-β -D-galactopyranoside ( 6 ), palmitic acid ( 7 ), and linoleic acid ( 8 ). The structures of the isolated compounds were assigned by 1D and 2D NMR. The crude extract exhibited moderate anti- Staphylococcus activity (MIC = 196.8 µg/mL), while compound 1 (kaempferol 3- O -gentiobioside) showed the strongest inhibitory effect (MIC = 8.3 µM), followed by compounds 2 and 3 (MIC = 10.2 and 11.2 µM, respectively). These compounds significantly reduced MRSA biofilm formation by up to 75.09% at sub-MIC concentrations ( p < 0.05). Checkerboard assays revealed synergistic interactions among compounds 1 , 2 , and 3 and between these compounds and gentamicin (FICI < 0.5), suggesting enhanced therapeutic potential when combined. An integrated computational approach combining protein-protein interaction (PPI) network analysis, molecular docking, and molecular dynamics (MD) simulations was employed. The PPI network analysis, constructed using the STRING and STITCH databases, revealed critical MRSA-associated targets and their interactions with bioactive compounds from S. muricatum . Network hub analysis identified key immune-regulatory and antibacterial resistance-related proteins, suggesting potential intervention points. Molecular docking results identified kaempferol 3-gentiobioside (compound 1 ) as the most potent inhibitor of APH(3’)-IIIa, with strong binding energy and interactions with key catalytic residues. Further 150 ns MD simulations confirmed the stability of the compound 1 -APH(3’)-IIIa complex, as evidenced by minimal RMSD fluctuations, sustained hydrogen bonding, stable protein compactness (Rg), and favorable potential energy values.